Synergistic effects of nucleopolyhedroviruses on larvicidal activity against Spodoptera litura and Helicoverpa armigera - Zihan Shi; Jing Li; Can Wang; Shaolong Wu; Wei-ai Zeng; Shiping Jia; Yusheng Wang; Yansong Xiao; Mi Li; Lin Tan (BioControl, 2026)

Host preference and mortality caused by the parasitoid Sclerodermus guani on different cerambycid species - Qun Yu; Shuang Li; Yu-Jun Kong; Zuo-Xiang Sun; Dan-Dan Cao; Jian-Rong Wei (BioControl, 2024)

Beauveria bassiana (Ascomycota: Hypocreales) spores carried by Scleroderma guani (Hymenoptera: Bethylidae): a novel strategy for improving the control efficiency of Semanotus bifasciatus (Coleoptera: Cerambycidae) in the field - Jian-Yong Zeng; Jia-Wei Bai; Hua-Ling Wang; Xiao-Yu Su; Xue-Fei Wang; Ning-Ning Fu; Hui-Ping Li (BioControl, 2024)

Pathogenicity characteristics of the entomopathogenic fungus Cordyceps javanica IJ-tg19 to Acyrthosiphon pisum - Di Wang; Pei-Xiang Xing; Hong-Liang Diao; Wen-Wen Zhou; Xian-Wei Li; Li-Jun Zhang; Rui-Yan Ma (BioControl, 2023)

Assessment of Beauveria bassiana for the biological control of corn borer, Ostrinia furnacalis, in sweet maize by irrigation application - Mengxia Feng; Yunyue Zhang; Brad Steven Coates; Qian Du; Yuebo Gao; Lili Li; Haibin Yuan; Wei Sun; Xue Chang; Shuxiang Zhou; Yangzhou Wang (BioControl, 2023)
Kernels of sweet maize are directly consumed by humans. This high value crop is grown in arid and semi-arid regions of western Jilin Province, China where trickle irrigation is widely used and larvae of the corn borer, Ostrinia furnacalis Guenée (Lepidoptera: Crambidae), can cause significant kernel damage. Low humidity in arid regions is less conducive to the efficacy of the biological control agent, Beauveria bassiana (Balsamo) Vuillemin (Hypocreales: Cordycipitaceae). Simulated semi-arid conditions in greenhouse experiments were conducted comparing B. bassiana application on a granule carrier or in aqueous suspension to sweet maize. Applications of B. bassiana adhered to granules and in suspension reduced O. furnacalis leaf feeding damage, number of boreholes and tunneling length. Treatments with a granular carrier showed the most significant reductions in maize damage when applied once at whorl stage and in combination with a second application at the ear. The greatest reductions in boring and tunneling attributed to these treatments occurred at internodes around the ear. Although reduced damage was greatest following granular compared to aqueous applications, the latter also provided significant reductions in feeding damage compared to controls. This study demonstrates the utility of B. bassiana as a biological control agent for the reduction in damage caused by second-generation corn borer to sweet maize and existing irrigation equipment could be adapted for efficacious aqueous treatments by growers.

Evaluation of four artificial diets on demography parameters of Neoseiulus barkeri - Ya-Ying Li; Jin-Ge Yuan; Ming-Xiu Liu; Zi-Hui Zhang; Hai-Wei Zhou; Huai Liu (BioControl, 2021)

Continuous rearing of the predatory mite Neoseiulus californicus on an artificial diet - Zi-Wei Song; Duc Tung Nguyen; Dun-Song Li; Patrick De Clercq (BioControl, 2019)

Evaluation of Blattisocius dolichus (Acari: Blattisociidae) for biocontrol of root-knot nematode, Meloidogyne incognita (Tylenchida: Heteroderidae) - Chun-Ling Xu; Yong-Liang Chen; Xue-Nong Xu; Dong-Wei Wang; Hui Xie; En-Dong Wang; Dun-Song Li; Bao-Xin Zhang; Hou-Guo Qin (BioControl, 2014)

Biocontrol of Fusarium wilt disease in muskmelon with Bacillus subtilis Y-IVI - Qingyun Zhao; Wei Ran; Hui Wang; Xiang Li; Qirong Shen; Shengyuan Shen; Yangchun Xu (BioControl, 2013)

Host adaptation of a gregarious parasitoid Sclerodermus harmandi in artificial rearing - Li Li; Wei Wei; Zhudong Liu; Jianghua Sun (BioControl, 2010)